2015
DOI: 10.1183/16000617.00002915
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in systemic sclerosis: where do we stand?

Abstract: Interstitial lung disease (ILD) is common in systemic sclerosis (SSc) patients and despite recent advances in the treatment is, at present, the major cause of death. Today, an early diagnosis of ILD is possible, and is mandatory to improve the prognosis of the disease.Pulmonary function tests and high-resolution computed tomography remain the mainstay for the diagnosis of SSc-ILD, but there is a growing interest in lung ultrasound. Recently, the correlation between severity of fibrosis and some peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 83 publications
(96 reference statements)
6
95
1
8
Order By: Relevance
“…Moreover, acute exacerbation of ILD (AE-ILD) occurs at a 1-year frequency of 1.25%-3.3% and at a lifetime incidence of 7.2%, with a high mortality rate in patients with connective tissue disease (Park et al 2007;Suda et al 2009). Given the chronic nature of the disease, it has been considered that AE-ILD is not common in patients with SSc (Fan et al 2014;Cappelli et al 2015), but recent papers suggest that AE-ILD may occur even in patients with SSc (Park et al 2007;Bussone and Mouthon 2011;Tachikawa et al 2012;Ando et al 2013;Yasuoka 2016). However, little data are available regarding the prevalence of AE-ILD in Japanese patients with SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, acute exacerbation of ILD (AE-ILD) occurs at a 1-year frequency of 1.25%-3.3% and at a lifetime incidence of 7.2%, with a high mortality rate in patients with connective tissue disease (Park et al 2007;Suda et al 2009). Given the chronic nature of the disease, it has been considered that AE-ILD is not common in patients with SSc (Fan et al 2014;Cappelli et al 2015), but recent papers suggest that AE-ILD may occur even in patients with SSc (Park et al 2007;Bussone and Mouthon 2011;Tachikawa et al 2012;Ando et al 2013;Yasuoka 2016). However, little data are available regarding the prevalence of AE-ILD in Japanese patients with SSc.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the number of B-lines seen on LUS increased consistently with the growing extent of parenchymal changes on CT. 36 Increased number of B-lines was also shown to be a sensitive marker of ILD and to correlate significantly with HRCT scores in rheumatoid arthritis and patients with SSc. 37,38 In addition, the distance between each of two adjacent B-lines was shown to correlate with the extent of the ILD on chest HRCT Note: Data are presented as medians (IQR). P adj , P-value adjusted with the use of the Benjamini-Hochberg procedure.…”
Section: Relationship Between Tachypnea and Hrct As Well As Lus Finmentioning
confidence: 99%
“…However, patients undergoing HSCT showed a significant improvement in FVC and total lung capacity. HSCT treatment in scleroderma shows promise with respect to long term survival benefits in patients with SSc-ILD [81]. …”
Section: Promising Treatments For Ctd-ildmentioning
confidence: 99%